Further reduction of disqualification rates by additional MRI-targeted biopsy with transperineal saturation biopsy compared with standard 12-core systematic biopsies for the selection of prostate cancer patients for active surveillance - Radtke, Jan Philipp; Kuru, Timur Hasan; Bonekamp, David; Alt, Céline D.; Hatiboglu, Gencay; Boxler, Silvan; Pahernik, Sascha; Roth, Wilfried; Schlemmer, Heinz-Peter; Hohenfellner, Markus; Hadaschik, Boris (Prostate cancer and prostatic diseases, 2016)
Background:Active surveillance (AS) is commonly based on standard 10-12-core prostate biopsies, which misclassify ~50% of cases compared with radical prostatectomy. We assessed the value of multiparametric magnetic resonance imaging (mpMRI)-targeted transperineal fusion-biopsies in men under AS.Methods:In all, 149 low-risk prostate cancer (PC) patients were included in AS between 2010 and 2015. Forty-five patients were initially diagnosed by combined 24-core systematic transperineal saturation biopsy (SB) and MRI/transurethral ultrasound (TRUS)-fusion targeted lesion biopsy (TB). A total of 104 patients first underwent 12-core TRUS-biopsy. All patients were followed-up by combined SB and TB for restratification after 1 and 2 years. All mpMRI examinations were analyzed using PIRADS. AS was performed according to PRIAS-criteria and a NIH-nomogram for AS-disqualification was investigated. AS-disqualification rates for men initially diagnosed by standard or fusion biopsy were compared using Kaplan-Meier estimates and log-rank tests. Differences in detection rates of the SB and TB components were evaluated with a paired-sample analysis. Regression analyses were performed to predict AS-disqualification.Results:A total of, 48.1% of patients diagnosed by 12-core TRUS-biopsy were disqualified from AS based on the MRI/TRUS-fusion biopsy results. In the initial fusion-biopsy cohort, upgrading occurred significantly less frequently during 2-year follow-up (20%, P<0.001). TBs alone were significantly superior compared with SBs alone to detect Gleason-score-upgrading. NPV for Gleason-upgrading was 93.5% for PIRADS⩽2. PSA level, PSA density, NIH-nomogram, initial PIRADS score (P<0.001 each) and PIRADS-progression on consecutive MRI (P=0.007) were significant predictors of AS-disqualification.Conclusions:Standard TRUS-biopsies lead to significant underestimation of PC under AS. MRI/TRUS-fusion biopsies, and especially the TB component allow more reliable risk classification, leading to a significantly decreased chance of subsequent AS-disqualification. Cancer detection with mpMRI alone is not yet sensitive enough to omit SB on follow-up after initial 12-core TRUS-biopsy. After MRI/TRUS-fusion biopsy confirmed AS, it may be appropriate to biopsy only those men with suspected progression on MRI.